The effects of intrathecal administration of bupivacaine or ropivacaine following administration of propofol in dogs undergoing ovariohysterectomy - YAYLA S; KAÇAR C; KILIÇ E; KAYA S; KURU M; ERMUTLU CŞ; ÖZAYDIN İ; HÜSEYİNOĞLU Ü; ÖĞÜN M (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2017)
The aim of this study was to compare intrathecal (IT) administration of bupivacaine and ropivacaine after propofol was given to dogs undergoing ovariohysterectomy operation. After propofol was administered to 16 dogs, IT anesthesia was performed with either 20 mg of bupivacaine (bupivacaine group, BG, n=8) or 30 mg ropivacaine (ropivacaine group, RG, n=8) in the lumbosacral space in this randomized, prospective, clinical trial. Noninvasively systolic, diastolic and mean arterial blood pressure, heart rate, respiratory rate and rectal temperatures were recorded after propofol and up to 150 min after IT injections. Onset, duration and the extent of sensory block were determined by using the needle prick during the ovariohysterectomy operation. The duration of IT anesthesia (BG: 89.5±7.6 min; RG: 64.75±6.8 min) was significantly different between the groups (P<0.05). The values in each group were within the reference range although there were differences in terms of arterial blood pressure (systolic, diastolic and mean), heart rate, respiratory rate and rectal temperatures. In conclusion, this study showed that IT bupivacaine and ropivacaine following administration of propofol can provide safe and effective anesthesia in dogs undergoing ovariohysterectomy operations